Number Names: Do They Count?. Issue 1 (2nd January 2019) - Mostert, Ingrid
Abstract : A number of post-colonial countries in Africa have introduced home language instruction for the initial years of schooling. This policy is particularly challenging in mathematics, as there is a paucity of research on how the linguistic features of African languages might be leveraged for the teaching and learning of mathematics. This paper examines the linguistic features of certain African languages, pertaining to number names, by describing five linguistic features of one particular African language, isiXhosa. The five features are: syntactical category, transparency, regularity, length of words and differences between spoken and written language. Different early-grade mathematics texts in English and isiXhosa are compared to explore the implications of these features for the learning and teaching of mathematics. The study concludes that there are both constraints and affordances of learning number names in isiXhosa and other related African languages and suggests how the affordances might be leveraged and the constraints mitigated.